The first WHO reference panel for Infliximab anti-drug antibodies: a step towards harmonizing therapeutic drug monitoring - Wadhwa, Meenu; Cludts, Isabelle; Atkinson, Eleanor; Rigsby, Peter (Frontiers in Immunology, 2025)
Immunogenicity testing for anti-drug antibodies (ADA) is mandatory for regulatory approval of a biotherapeutic and can, in some instances, continue post-licensure. Typical examples are TNF inhibitors where biotherapeutic and ADA levels are relevant in clinical decision-making for optimal patient therapy. However, challenges with non-comparability of results due to plethora of bioanalytical techniques and the lack of standardization has hindered ADA monitoring in clinical practice. Two human anti-infliximab monoclonal antibodies (A, B) with defined characteristics were therefore lyophilized and assessed for suitability as a reference panel for ADA assays in an international study. Binding assays included the simple ELISA and common electrochemiluminescence (ECL) to the rare antigen binding test and lateral flow assays. For neutralisation, competitive ligand binding and reporter-gene assays were employed. Sample testing (e.g., antibodies, sera) showed differential reactivity depending on the assay and sample. Estimates for ADA levels using in-house standards varied substantially among assays/laboratories. In contrast, using antibody A for quantitating ADA levels reduced the interlaboratory variability and provided largely consistent estimates. The degree of harmonization was dependent on the assay, sample and the laboratory. Importantly, antibody A allowed ADA detection when missed using in-house standards. Recognition of sample B varied, possibly due to its fast dissociation. Overall, the panel comprising A (coded 19/234) and B (coded 19/232) was suitable and established by the WHO Expert Committee on Biological Standardization in October 2022 as the WHO international reference panel for infliximab ADA assays. Sample A (coded 19/234) with an arbitrarily assigned unitage of 50,000IU/ampoule for binding activity and 50,000 IU/ampoule for neutralising activity is intended as a ‘common standard’ for assay characterization and where possible for calibration of anti-infliximab preparations to facilitate comparison and harmonization of results across infliximab ADA assays. Sample B (19/232) with its unique characteristics and variable detection but no assigned unitage is intended for assessing the suitability of the assay for detecting ADAs with fast dissociation. It is anticipated that this panel would help towards selecting and characterizing suitable assays, benchmarking of in-house standards where feasible and in harmonizing ADA assays used in clinical practice for better patient outcome globally.